Adeia in Fifth-Century Athens. (November 2021) - Esu, Alberto
Abstract: This article discusses the rationale of adeia (immunity) in the fifth-century Athenian legal system. It argues that adeia was designed to grant a temporary suspension of the effect of a law in exceptional circumstances without allowing for any permanent legal change. This article explores the origin of adeia and the relevant ideology underpinning the legal procedure. It provides a comprehensive reconstruction of the legal procedure and analyses the extensive use of adeia for collecting information during the investigation of the profanation of the Mysteries and the mutilation of the herms in 415 BC. This article also discusses the implications of the use of adeia for public investigation and emergency powers in Classical Athens.